2017
DOI: 10.1111/scd.12227
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the proposed association between DED and gluten‐free diet introduction in celiac children

Abstract: A strong association between celiac disease (CD) and dental enamel defects (DEDs) have been extensively reported, however, the nature of this relationship is still unclear. The aim of this study was to evaluate DEDs phenotype in CD individuals according to the time they were introduced to a gluten-free diet (GFD). Forty-five CD individuals were examined by a pediatric dentist. DEDs were classified according to the type of affected teeth. CD individuals were classified into two groups (with or without DEDs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Coeliac disease‐associated developmental enamel defects (CeD‐DED) are symmetrical, time‐synchronized, often horizontal defects that may develop during amelogenesis in children with untreated CeD. Development of normal enamel reoccurs following treatment of active disease with a gluten‐free diet . We and others have reported that IgG and IgA to gliadin cross‐react with amelogenin (AMEL) (the abbreviation ‘AMEL’ is used for both amelogenin X and Y isoforms in this paper, unless referring to the specific X isoform of amelogenin, in which case the abbreviation ‘AMELX’ is used) in adults and paediatric subjects with untreated CeD.…”
mentioning
confidence: 99%
“…Coeliac disease‐associated developmental enamel defects (CeD‐DED) are symmetrical, time‐synchronized, often horizontal defects that may develop during amelogenesis in children with untreated CeD. Development of normal enamel reoccurs following treatment of active disease with a gluten‐free diet . We and others have reported that IgG and IgA to gliadin cross‐react with amelogenin (AMEL) (the abbreviation ‘AMEL’ is used for both amelogenin X and Y isoforms in this paper, unless referring to the specific X isoform of amelogenin, in which case the abbreviation ‘AMELX’ is used) in adults and paediatric subjects with untreated CeD.…”
mentioning
confidence: 99%
“…These inconsistencies may be caused by several factors, such as different age at CD diagnosis, strict adherence to a gluten-free diet and its duration as well as the type of population represented in the study. 7,16,21,27 Cheng et al 28 also found that a younger age of a patient corresponds to more pronounced defects. It was concluded that younger age at diagnosis may contribute to fewer and less severe CD-related enamel defects.…”
Section: Discussionmentioning
confidence: 97%
“…The overall prevalence of enamel defects among children suffering from CD varies from 17.9% to 83.5%. These inconsistencies may be caused by several factors, such as different age at CD diagnosis, strict adherence to a gluten‐free diet and its duration as well as the type of population represented in the study 7,16,21,27 . Cheng et al 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The factors contributing to DEDs IIe Immune damage, nutritional disorders, and genetic factors. DEDs are considered specific if they are present symmetrically and chronologically on both sides and distributed in all four quadrants of the permanent teeth, with incisors and molars as the most commonly affected teeth [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest a possible common genetic basis or the possibility that enamel defects are caused by nutritional deficiencies related to CD [ 88 ].…”
Section: Discussionmentioning
confidence: 99%